The Role of Ti and Lewis Acidity in Manganese Oxide Octahedral Molecular Sieves Impregnated with Titanium in Oxidation Reactions - Fitri Hayati; Sheela Chandren; Halimaton Hamdan; Hadi Nur (Bulletin of Chemical Reaction Engineering & Catalysis, 2014)
Octahedral manganese oxide molecular sieves (OMS-2) was prepared by precipitation method and modified by impregnation of titanium with different titanium/manganese (Ti/Mn) ratio. It was also discovered that Ti/Mn ratio of less than 0.5 still retains the original pure cryptomelane structure of OMS-2. However, for sample with Ti/Mn ratio of more than 0.5, some rutile phases of titania (TiO2) can be detected together with the cryptomelane phase. Lewis acid sites were also observed in the titanium modified OMS-2 (Ti-OMS-2). Ti-OMS-2 was then used as catalysts for the oxidation of cyclohexane, cyclohexene and styrene, where Ti-OMS-2 with Ti/Mn ratio of 0.67 was most active in all three of the oxidation reactions as compared to TiO2 and OMS-2. The results suggest that both titanium sites in framework and non-framework and the Lewis acidity created by the impregnation of Ti, increased the activity of OMS-2 in oxidation reactions. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)